Pengaruh Media Gambar Terhadap Kemampuan Membaca Permulaan Siswa Kelas 1 Sekolah Dasar - Putri, Putri; Misrina, Misrina; Hayati Siregar, Rahma (Jurnal keilmuan dan Kependidikan dasar, 2025)
This study aims to analyze the effect of picture media on the beginning reading ability of first-grade elementary school students. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The research population consisted of all first-grade students of SD Negeri 8 Tanah Luas, North Aceh, totaling 46 students, who were selected as the sample through a total sampling technique. Class IB was assigned as the experimental group, while Class IA served as the control group. The research instrument was a beginning reading ability test administered in the form of a pretest and posttest. Data were analyzed using descriptive statistics and an Independent Samples t-test with the assistance of SPSS. The results showed that the mean posttest score of the experimental group was higher than that of the control group (86.74 > 74.61). In addition, the obtained value of tcalculated > ttable​ (4.392 > 1.680) with a significance level of 0.000 < 0.05 indicated a statistically significant difference between the two groups. Therefore, it can be concluded that the use of picture media has a positive and significant effect on the beginning reading ability of first-grade elementary school students.